Pemanfaatan Sistem Informasi Pengelolaan Data Prestasi Siswa Bagi Sekolah Menengah Atas - Laqma Dica Fitrani; Mohammad Al Hafidz; Muhammad Septama Prasetya; Adeliafitri Nabillah; Muhammad Kevin Dwie Cahyo (STMIK Royal, 2024)
SMAN 1 Waru is experiencing rapid development, particularly in this digital era, with its students achieving notable success in sports, science, and arts. However, despite these achievements, the management of such accomplishments remains inadequate, rely-ing on manual systems. Consequently, the collection and recording of student achieve-ment data at SMAN 1 Waru are disorganized and often not up to date. Recognizing this issue, the community service team has developed an information system to manage stu-dent achievement data. This system includes comprehensive training to facilitate the ef-ficient processing of student achievements for both internal and external purposes, such as accreditation. The training session took place on March 28, 2024, at SMAN 1 Waru's computer laboratory and was attended by 35 students, website administrators, and three teachers. The training employed various methods, including lectures, practical exercises, and discussions. All participants demonstrated a clear understanding of the application's usage, as evidenced by their improved pre-test and post-test scores. Statistical analysis using the t-test confirmed the significance of this improvement, indicating that the train-ing effectively enhanced participants' understanding of using the student achievement website. Furthermore, the success of the training is reflected in the records of achieve-ment data inputted by the participants. Keywords: achievement data; information system; website.